The growth, photosynthetic pigments and essential oil composition of monocropped and intercropped lemon balm with yarrow - Thaís Cristina Silva; José Eduardo Brasil Pereira Pinto; Fernanda Ventorim Pacheco; Heitor Luiz Heiderich Roza; Diogo Mendes da Silva Lordêllo; Suzan Kelly Vilela Bertolucci (Acta Scientiarum. Agronomy, 2018)
The purpose of this study was to assess the influence of lemon balm intercropping with yarrow on the vegetative growth, photosynthetic pigments and essential oil contents as well as the chemical composition of essential oils. Accordingly, the lemon balm and yarrow monocroppings were compared to the intercropping of both species. The plants were cultivated for 120 days under field conditions. The experimental design followed randomized blocks with seven repetitions. Growth was assessed through the accumulation of shoot dry matter and through the leaf area. The photosynthetic pigment content was set based on the fully expanded leaves from five plants in each treatment. The essential oil was extracted through the hydrodistillation of the lemon balm leaves and yarrow leaflets dehydrated in a forced ventilation oven at 40°C. The chemical analyses of the essential oils were performed using GC-FID and GC-MS. Intercropping showed a reduction of vegetative growth. However, intercropping increased the lemon balm essential oil content. On the other hand, these parameters did not change in yarrow. There were variations in the level of chemical constituents in lemon balm and yarrow essential oils, which were more evident in the major constituents.